Pré-concentração por extração em ponto nuvem para determinação de cádmio em amostras de bebidas por espectrometria de absorção atômica como forno tubular na chama e aerossol térmico - Rezende, Helen Cristine de (2010)
In this work, it was evaluated extraction/preconcentration cloud point procedure for cadmium determination in soft drinks samples stored in polyethylene terephthalate (PET) packaging and detection by thermospray flame furnace atomic absorption spectrometry (TS -FF-AAS). For the cloud point preconcentration procedure were used Triton X-114 as surfactant, PAN as complexing agent and sodium chloride as electrolyte, to induce the formation of point cloud without heating. The parameters complexation time, Triton X-114, PAN and sodium chloride concentrations were optimized using factorial designs and surface response methodologies. For TS-FF-AAS, a volume of 100 mL was introduced into the hot Ni tube using water carrier at a flow rate of 0.4 mL min-1. Under the optimized conditions were obtained detection limit of 0.0178 mg L-1, quantification limit of 0.0595 mg L-1, relative standard deviation (RSD) of 4.1% for n = 6 and an enhancement factor of 55.5. The accuracy was checked by addiction-recovery experiments and the method was applied to samples of soft drinks.